Human papillomavirus in amniotic fluid - Swan David C; Tucker Ruth; Lee Daisy R; Roulston Diane; Bailey Joanne M; Ruffin Mack T; Unger Elizabeth R (BMC, 2006)
Abstract Background There is evidence to suggest that human papillomavirus (HPV) can cross the placenta resulting in in-utero transmission. The goal of this study was to determine if HPV can be detected in amniotic fluid from women with intact amniotic membranes. Methods Residual amniotic fluid and cultured cell pellets from amniocentesis performed for prenatal diagnosis were used. PGMY09/11 L1 consensus primers and GP5+/GP6+ primers were used in a nested polymerase chain reaction assay for HPV. Results There were 146 paired samples from 142 women representing 139 singleton pregnancies, 2 twin pregnancies, and 1 triplet pregnancy. The women were 78% Caucasian, 5% African American, 14% Asian, and 2% Hispanic. The average age was 35.2 years with a range of 23-55 years. All samples were β-globin positive. HPV was not detected in any of the paired samples. Conclusion Given the age range, race, and ethnicity of the study population, one would anticipate some evidence of HPV if it could easily cross the placenta, but there was none.